The phenomenon of traditional philanthropy through the voluntary sector in shaping community identity - Kurniati, Pat; Sapriya, Sapriya; Darmawan, Cecep; Rolando P., Quinones Jr; Putra, Haris Maiza (Universitas Negeri Yogyakarta, 2023)
The role of the state is needed to suppress illegal philanthropic practices, how the state can make Pancasila a